Assessing iMET-XQ Performance and Optimal Placement on a Small Off-the-Shelf, Rotary-Wing UAV, as a Function of Atmospheric Conditions - Sytske K. Kimball (Atmosphere, 2020)
The accuracy and precision of iMET-XQ (InterMET Inc., Grand Rapids, MI, USA) temperature measurements in ten different locations on an off-the shelf rotary-wing unmanned aerial vehicle (rw-UAV) were assessed, as a function of atmospheric conditions. The rw-UAV hovered near an instrumented South Alabama Mesonet tower. The mean ± standard deviation of all the temperature differences between the tower and the ten iMET-XQ sensors for all experiments are −0.23 °C ±0.24 °C. Both the UAV and the environment influence the accuracy and precision of the iMET-XQ temperature measurements. Heat generated by the electronic components within the UAV body has a significant influence on the iMET-XQ temperature measurements, regardless of solar radiation conditions, and is highly dependent on wind direction. Electronic components within the UAV body heat up and can cause sensors downwind from the UAV body to record temperatures that are too warm, even if the sensors are aspirated by propeller wash. iMET-XQ sensors placed on rotor arms not near UAV body heat sources, and properly aspirated by propeller wash, perform well. Measurements from iMET-XQ sensors suspended below the UAV are also accurate. When using an off-the-shelf UAV for atmospheric temperature sensing, the electronic components inside the body of the UAV must be properly located. It is recommended that multiple sensors are placed on the UAV. Sensor redundancy will mitigate data loss in case of malfunction during flight and the identification of poorly performing sensors.